PENGARUH BRAND AWARENESS, TRANSPARANSI, DAN KEPERCAYAAN TERHADAP KEPUTUSAN MENYALURKAN ZIS DI KITABISA.COM - Azizah, Nur; Hasbi, Sahlan; Yetty, Fitri (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
Financial Technology is evidence of innovation in the financial services sector that makes it very easy for the public. Fintech is not only used for buying and selling transactions only. But it can be used as a crowdfunding platform conducted online. One of the most popular crowdfunding platforms operating in Indonesia in terms of ZIS fundraising is crowdfunding Kitabisa.com. This study aims to explain the effect that occurs on brand awareness (X1), transparency (X2), and trust (X3) on people's decisions to distribute ZIS through crowdfunding Kitabisa.com (Y). The method used is quantitative methods. The samples used in the study were users of the Kitabisa.com platform, with a total sample of 121 people in the Jabodetabek area. The data used is primary. This study uses a questionnaire instrument and a Likert scale. This study uses multiple linear regression analysis methods and using SPSS Statistics version 23. The results of this study indicate that the variables of brand awareness, transparency, and trust have a significant partial and simultaneous effect on the public's decision to distribute ZIS through crowdfunding Kitabisa.com.